Measurement Model of Reasoning Skills among Science Students Based on Socio Scientific Issues (SSI) - MOHD AFIFI BAHURUDIN SETAMBAH (Indonesian Research Journal in Education |IRJE|, 2018)
The lack of reasoning skills has been recognized as one of the contributing factors to the declined achievement in the Trends in Mathematics and Science Studies (TIMSS) and Programme for International Student Assessment (PISA) assessments in Malaysia. The use of socio-scientific issues (SSI) as a learning strategy offers the potential of improving the level of students' reasoning skills and consequently improves students’ achievement in science subjects. This study examined the development of a measurement model of reasoning skills among science students based on SSI using the analysis of moment structure (AMOS) approach before going to second level to full structured equation modelling (SEM). A total of 450 respondents were selected using a stratified random sampling. Results showed a modified measurement model of reasoning skills consisting of the View Knowledge (VK) was as a main construct. The items that measure the level of pre-reflection of students fulfilled the elements of unidimensionality, validity, and reliability. Although the level of student reasoning skills was still low but this development of measurement model could be identified and proposed teaching methods that could be adopted to improve students’ reasoning skills.